Vanderbylia kashmiriana sp. nov. (Polyporales, Polyporaceae) from Azad Jammu & Kashmir, Pakistan - Irfan, Uzma; Khalid, Abdul Nasir; Aziz, Abida (Phytotaxa, 2023)
A novel wood rotting species of genus Vanderbylia occurring at the base of Zanthoxylum armatum is described from mixed vegetation of District Bhimber, Azad Jammu & Kashmir, based on phylogenetic analyses of ITS and LSU sequences. Further, distinct morpho-anatomical characters confirmed the novelty of the species as Vanderbylia kashmiriana. The taxon is characterized by pileate and corky basidiomata, a dimitic hyphal system with peculiar, extensively branched arboriform hyphae, globose to sub-globose to ellipsoid, hyaline, apiculate, strongly dextrinoid basidiospores, sub-clavate to obovoid basidia with the variable number of sterigmata (1–4), clavate to obclavate to ventricose to tubular, apically encrusted, granular, clamped cystidia. This is the first described species of the genus Vanderbylia from Pakistan.